A systematic approach to identify STRE-binding proteins of the gsn glycogen synthase gene promoter in Neurospora crassa - Freitas, Fernanda Zanolli [UNESP]; Chapeaurouge, Alex; Perales, Jonas; Bertolini, Maria Celia [UNESP] (Wiley-v C H Verlag Gmbh, 2008)
The gene encoding glycogen synthase in Neurospora crassa (gsn) is transcriptionally down-regulated when mycelium is exposed to a heat shock from 30 to 45 degrees C. The gsn promoter has one stress response element (STRE) motif that is specifically bound by heat shock activated nuclear proteins. In this work, we used biochemical approaches together with mass spectrometric analysis to identify the proteins that bind to the STRE motif and could participate in the gsn transcription regulation during heat shock. Crude nuclear extract of heat-shocked mycelium was prepared and fractionated by affinity chromatography. The fractions exhibiting DNA-binding activity were identified by electrophoretic mobility shift assay (EMSA) using as probe a DNA fragment containing the STRE motif DNA-protein binding activity was confirmed by Southwestern analysis. The molecular mass (MM) of proteins was estimated by fractionating the crude nuclear extract by SDS-PAGE followed by EMSA analysis of the proteins corresponding to different MM intervals. Binding activity was detected at the 30-50 MM kDa interval. Fractionation of the crude nuclear proteins by IEF followed by EMSA analysis led to the identification of two active fractions belonging to the pIs intervals 3.54-4.08 and 6.77-7.31. The proteins comprising the MM and pI intervals previously identified were excised from a 2-DE gel, and subjected to mass spectrometric analysis (MALDI-TOF/TOF) after tryptic digestion. The proteins were identified by search against the MIPS and MIT N. crassa databases and five promising candidates were identified. Their structural characteristics and putative roles in the gsn transcription regulation are discussed.
Keywords: EMSA; gsn promoter; heat shock; Neurospora crassa; TRE